Assessment of SERS-active nanosensors as a tool for pH measurements within living cells - Engman, Helena E. M. (The University of Edinburgh, 2022)
Intracellular and intraorganellar pH is an essential aspect of the maintenance of proper cellular functions. Measurement of pH within cells could therefore elucidate crucial information regarding cell behaviour and pathology. Surface Enhanced Raman spectroscopy (SERS) is a method which has shown great potential as a method for pH measurement. SERS in combination with gold nanoparticles (AuNP) covalently bound to a pH sensitive molecule, 4-mercaptobenzoic acid (MBA), was assessed as a method to measure pH within live mammalian cells. The protonation states of MBA can be detected via the change of pH sensitive peaks within its Raman spectrum, and this information can be used to determine the pH. Within this thesis the MBA-AuNP were characterised in terms of cytotoxicity, reversibility, intracellular localisation, and capability of the MBA-AuNPs to measure pH within healthy and disease model mammalian cells, specifically human embryonic stem cells and primary sheep subventricular zone (SVZ) cells from Batten Disease affected and unaffected animals, respectively. The sensor was shown to cause no decrease in cell viability or proliferation and were able to respond to pH changes in a reversible manner. Large numbers of MBA-AuNP were shown to accumulate in perinuclear regions in close association with vesicles positive for the lysosomal marker LAMP1, but not LAMP2. Furthermore, assessment of pH perturbations in a cell model for the lysosomal storage disorder, Batten Disease, showed that the sensors are capable of discrimination of slight physiological pH changes within lysosomes.
Keywords: Intracellular pH; Raman spectroscopy; Surface-enhanced Raman spectroscopy; SERS; stem cells; SERS-active nanosensors